Telaah Makna Gramatis dan Psikologis dalam Syair Abdul Muluk Karya Raja Ali Haji - Hadiwijaya, Hadiwijaya; Sarwono, Sarwit; Yulistio, Didi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to describe the meanings obtained from the results of grammatical interpretation and psychological interpretation of the author towards Syair Abdul Muluk by Ali Haji using Schleiermacher Hermeneutics. The research approach uses a qualitative approach with the hermeneutic method. The data collection technique uses documentation techniques in the form of Syair Abdul Muluk text by Ali Haji. The data analysis technique is done by reading poetry, identifying each event, interpreting the meaning, analyzing the relationships between the elements of poetry, and concluding meaning. Based on the from the research shows that the meaning contained in Syair Abdul Muluk by Ali Haji is that women can play a role like men in maintaining loyalty and achieving goals. Women can also be powerful even though they must condition themselves outside their nature as women. For Raja Ali Haji in the perspective of national culture and society, religion is a binding knot for various social levels in fostering culture.